"Antifragility" versus "Seneca Cliff" – Crisis Discourse and Its Metaphors - Solska, Ewa (Sensus Historiae, 2023)
The paper focuses on the issue of crisis, currently considered in the context of collapsology discourse and scientific research in the system dynamics approach. It also reminds us of the conceptual category of crisis (which appears in historical research already in the mid-19th century). Starting from these references, the metaphorical dimension of the contemporary crisis discourse is discussed (mainly the concept of “Seneca cliff”), considering crisis as a “traveling concept” within transdisciplinary research model and metascience. Discursive threads of dealing with the crisis situation are also considered in relation to metaphors of “antifragility” and “Seneca strategy.”